2019
DOI: 10.22543/7674.62.p232236
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholic liver cirrhosis, more than a simple hepatic disease – A brief review of the risk factors associated with alcohol abuse

Abstract: Liver cirrhosis is a significant public health problem, being an important cause of mortality and morbidity, responsible for approximately 1.8% of the total number of deaths in Europe. Chronic alcohol consumption is the most common cause of liver cirrhosis in developed countries. Europe has the highest level of alcohol consumption among all the global World Health Organisation (WHO) regions. In this paper, we briefly review major factors leading to excessive alcohol consumption in order to draw attention to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
1
0
1
Order By: Relevance
“…Alcohol abuse is thought to be affected by genes encoding ethanol-metabolizing enzymes, psychological and social factors (Micu et al, 2019). With the identified allele and genotype frequencies of ADH1B rs1229984, ADH1C rs698, and ALDH2 rs671 showed that these SNPs were in Hardy-Weinberg equilibrium and have been inherited stably in the Vietnamese population living in Northeast region of Vietnam (p>0.05) (Table 2).…”
Section: Discussionmentioning
confidence: 98%
“…Alcohol abuse is thought to be affected by genes encoding ethanol-metabolizing enzymes, psychological and social factors (Micu et al, 2019). With the identified allele and genotype frequencies of ADH1B rs1229984, ADH1C rs698, and ALDH2 rs671 showed that these SNPs were in Hardy-Weinberg equilibrium and have been inherited stably in the Vietnamese population living in Northeast region of Vietnam (p>0.05) (Table 2).…”
Section: Discussionmentioning
confidence: 98%
“…With the relatively high prevalence of ADH1B*2/*2, ADH1C*1/*1, ALDH2*1/*2 and ALDH2*2/*2 in study subjects, they are predicted to be at increased risk of diseases if they abuse alcohol. According to Micu et al, (2019), in addition to ethanol-metabolizing enzymes involved in alcohol abuse leading to alcohol dependence, there are also psychological and social factors. Vietnam is currently assessed as a country with high alcohol consumption, especially among men.…”
Section: Discussionmentioning
confidence: 99%
“…Lạm dụng đồ uống có ethanol là yếu tố gây nguy cơ tử vong cao và nhiều bệnh tật ở người, số ca tử vong do ung thư liên quan đến sử dụng đồ uống có ethanol chiếm 4,2% tổng số ca ung thư vào năm 2016 [2]. Theo Micu và các cộng sự [3], ngoài yếu tố di truyền là các enzyme chuyển hóa ethanol (ADH1B, ALDH2) liên quan đến lạm dụng rượu còn có yếu tố tâm lý và xã hội.…”
Section: Mở đầU *unclassified